Aligning ecological compensation policies with the Post‐2020 Global Biodiversity Framework to achieve real net gain in biodiversity. Issue 3 (27th January 2022) - Simmonds, Jeremy S.; von Hase, Amrei; Quétier, Fabien; Brownlie, Susie; Maron, Martine; Possingham, Hugh P.; Souquet, Mathieu; zu Ermgassen, Sophus O. S. E.; ten Kate, Kerry; Costa, Hugo M.; Sonter, Laura J.
Abstract: Increasingly, government and corporate policies on ecological compensation (e.g., offsetting) are requiring "net gain" outcomes for biodiversity. This presents an opportunity to align development with the United Nations Convention on Biological Diversity Post‐2020 Global Biodiversity Framework's (GBF) proposed ambition for overall biodiversity recovery. In this perspective, we describe three conditions that should be accounted for in net gain policy to align outcomes with biodiversity recovery goals: namely, a requirement for residual losses from development to be compensated for by (1) absolute gains, which are (2) scaled to the achievement of explicit biodiversity targets, where (3) gains are demonstrably feasible. We show that few current policies meet these conditions, which risks undermining efforts to achieve the proposed Post‐2020 GBF milestones and goals, as well as other jurisdictional policy imperatives to halt and reverse biodiversity decline. To guide future decision‐making, we provide a supporting decision tree outlining net gain compensation feasibility.